Revisão bibliográfica de artigos com ratos espontaneamente hipertensivos (SHR) em pesquisas de modelo animal de TDAH - Portella, Gabriel Augusto Alexandre (2020)
Attention deficit hyperactivity disorder (ADHD) is the most common childhood disorder, which affects about 2.7% -31.1% of this population, also affecting about 4% of the adult population. Considering the social and educational losses that result from the disorder, it was necessary to recognize conditions that determine and alter their characteristic behaviors, with animal research being one of the strategies for producing knowledge about this condition. This research aimed to review the literature on the subject, based on the search for articles on animal models of TDHA developed with spontaneously hypertensive rats (SHR). The search was carried out in national and international journals, from 1999 to 2019, with research selected that met the criteria of 1) using SHR rats, 2) being experimental and 3) using procedures and concepts from the Behavior Analysis area. As a result of the search, 19 articles were selected, investigating different behaviors of the so-called symptomatic triad of TDHA; namely: impulsivity, inattention and hyperactivity. The articles were classified for their interest in producing data that would allow validating the animal model of TDHA with SHR rats, or for their interest in the intervention (behavioral and / or medication) of the disorder. Behavioral similarities were identified that indicate the model's face validity, requiring further studies to increase the reliability of its predictive and construct validity. Few studies in the present sample have proposed the use of typical behavior analysis concepts, so most of them discussed the effects of manipulated variables, through mediationist interpretations